Assessing Fiscal Policy Impact on Economic Growth: A Comparative Analysis of Indonesia and Turkey - Olanrewaju, Riliwan Olalekan (Universitas Islam Internasional Indonesia, 2024)
The study involves the application of Vector Error Correction Models (VECM) to analyze macroeconomic dimension of fiscal policy on economic growth in Indonesia and Turkey. Furthermore, it attempts to depict the paths of fiscal policy and GDP evolution in the two economies by providing data for the period 1980-2022. It uses Augmented Dickey Fuller (ADF) tests and Johansen co-integration tests to check against the stationarity and the long-run relationships between fiscal policy variables and economic growth. The result of Granger causality analysis was used to address the two-way relationship between these variables. Data discloses that the fiscal policy of Indonesia does not significantly affects economic development directly, as Turkey’s case where government expenditure does have a positive relationship with economic growth in the short term. Despite the common unstable connection between government participation, government revenue and economic growth, there exists a long-term inimical correlation in both countries. The results of the study indicate the impact of fiscal policy as non-immediate measure is not effective with regards to Indonesia economic growth. This calls attention to the role of resource reallocation in creating a lasting development rate. That is why the relationship between public spending and short-term growth shows significant effectiveness of certain fiscal policy monetary measures aimed at increasing the rates of material production and growth in the country. The research indicates that long period of government expenditure maybe unbeneficial for developing economies. Contrary to this, it is governments’ duty to determine the etymologically sound methodologies of prudent fiscal plans that will enable privatization, investments, and economic growth.